Analysis of the endogenous peptide profile of milk: Identification of 248 mainly casein-derived peptides - Baum, Florian; Fedorova, Maria; Ebner, Jennifer; Hoffmann, Ralf; Pischetsrieder, Monika (Journal of Proteome Research, 2013)
Milk is an excellent source of bioactive peptides. However, the composition of the native milk peptidome has only been partially elucidated. The present study applied matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) directly or after prefractionation of the milk peptides by reverse-phase high-performance liquid chromatography (RP-HPLC) or OFFGEL fractionation for the comprehensive analysis of the peptide profile of raw milk. The peptide sequences were determined by MALDI-TOF/TOF or nano-ultra-performance liquid chromatography-nanoelectrospray ionization-LTQ-Orbitrap-MS. Direct MALDI-TOF-MS analysis led to the assignment of 57 peptides. Prefractionation by both complementary methods led to the assignment of another 191 peptides. Most peptides originate from αS1-casein, followed by β-casein, and α S2-casein. κ-Casein and whey proteins seem to play only a minor role as peptide precursors. The formation of many, but not all, peptides could be explained by the activity of the endogenous peptidases, plasmin or cathepsin D, B, and G. Database searches revealed the presence of 22 peptides with established physiological function, including those with angiotensin-converting- enzyme (ACE) inhibitory, immunomodulating, or antimicrobial activity. © 2013 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2013.nat.dchph.llmch.analys_8
Keywords: bioactive peptides: milk; cathepsin; ESI-MS: caseins; HPLC prefractionation; MALDI-TOF-MS; OFFGEL fractionation; peptide profiling; plasmin